2022
DOI: 10.1155/2022/9711074
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Solution for Meal Delivery Routing Optimization on Time-Sensitive Customer Satisfaction

Abstract: The online-to-offline (O2O) meal delivery mode in which takeout meals are ordered online and delivered offline is recently emerging. The fast delivery of huge meal orders for time-sensitive customers imposes great challenges on O2O meal delivery platforms. This study establishes a two-stage solution for meal delivery routing optimization with the objective of maximizing time-sensitive customer satisfaction. In the first stage, a large number of meal orders are hierarchically classified and merged into delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…(1) We develop a multi-objective optimization model based on timesensitive heterogeneous customers to solve the MDRP, which considers both perspectives of improving customer time satisfaction and reducing delay penalty cost and riding cost. This study enriches previous works on MDRP [7,8,13]. (2) A novel waiting strategy with time-sensitive priority is proposed, which further extends the research methods of MDRP for handling dynamic meal orders.…”
Section: Low Time Sensitivitymentioning
confidence: 61%
See 4 more Smart Citations
“…(1) We develop a multi-objective optimization model based on timesensitive heterogeneous customers to solve the MDRP, which considers both perspectives of improving customer time satisfaction and reducing delay penalty cost and riding cost. This study enriches previous works on MDRP [7,8,13]. (2) A novel waiting strategy with time-sensitive priority is proposed, which further extends the research methods of MDRP for handling dynamic meal orders.…”
Section: Low Time Sensitivitymentioning
confidence: 61%
“…In order to avoid order delays caused by uncertain information during dynamic delivery, Ulmer et al [7] proposed an anticipatory customer assignment (ACA) policy, which introduced a postponement to improve the flexibility of order assignment and a time buffer to reduce decisions that may cause delays. Wang and Jiang [13] developed a two-stage optimization algorithm to study customer satisfaction with time-sensitive heterogeneity. They found that considering time-sensitive heterogeneity was effective in improving customer time satisfaction.…”
Section: Meal Delivery Routing Problemmentioning
confidence: 99%
See 3 more Smart Citations